Relationship Between Hemochromatosis Gene Mutations and Degree of Fibrosis in Liver Disease Associated with Chronic Hepatitis B and C. - Bagir, Gülay Simsek; Dogan, Ümit Bilge; Egesel, Türker; Canataroglu, Abdullah (Turkiye Klinikleri Journal of Medical Sciences, 2012)
Objective: There are various factors that affect the degree of liver fibrosis in chronic viral hepatitis (CVH). Deposition of iron in the liver is one of these factors. Although hemochromatosis gene (HFE) mutation is determined as heterozygote, it is thought that it causes deposition of iron in the liver. However, the effect of the deposition of iron as a result of HFE gene mutation that leads to the progression of fibrosis in patients with CVH is still uncertain. The purpose of this study is to evaluate the association of HFE gene mutations with serum iron indices and degree of fibrosis in patients with CVH. Material and Methods: The study enrolled 83 patients with chronic hepatitis B, 61 patients with chronic hepatitis C and 50 healthy controls. Fifty-two of the patients also had cirrhosis. AST, ALT, serum iron, ferritin and transferrin saturations were measured and the presence of HFE mutations were investigated for all individuals. Liver biopsy was performed to all patients. Histopathological findings in the liver were scored as necroinflammatory activity and fibrosis according to the Knodell scoring scale. Results: The C282Y mutations could not be detected in any individuals. H63D heterozygous and homozygous mutations were found but they did not differ between patients (n=29, 20.1%) and controls (n=14, 28%). Presence of H63D mutations was not associated with serum iron indices or the degree of hepatic fibrosis. Conclusion:Our results showed that H63D gene mutations do not have a significant role in the progression of fibrosis in CVH.